An effective surface modification of UHMWPE fiber for improving the interfacial adhesion of epoxy resin composites. Issue 4 (3rd January 2020) - Wang, Shicheng; Ma, Jinyang; Feng, Xia; Cheng, Jinxue; Ma, Xiao; Zhao, Yiping; Chen, Li
Abstract: Ultra high molecular weight polyethylene (UHMWPE) fiber composite was reinforced by coating a functional layer on the surface of the UHMWPE fiber to improve interfacial adhesion between the fiber and the resin matrix. In this work, tannic acid (TA)‐Na + composite modified UHMWPE fiber was used to improve moisture wettability and adhesion between the fiber and the resin. This approach had the advantages of being green, sustainable, lossless, low‐cost, and industrialized. The surface characteristics of UHMWPE fiber were investigated by Fourier transform infrared spectroscopy, X‐ray photoelectron spectroscopy, and scanning electron microscopy. The results show that the TA coating can improve the surface roughness, wettability, and adhesion of UHMWPE fiber, thereby improving the interface properties between fiber and resin. The tensile strength of interfacial shear strength and macro‐composites of TA coating UHMWPE fiber increased by 43.3% and 28%, respectively.